A Study on Junior High School Physical Education Teachers’ Understanding of The Implementation of The Merdeka Curriculum - Denus Pranandi; Aridhotul Haqiyah; Tatang Iskandar (Universitas Negeri Semarang, 2025)
Teachers must always improve pedagogical competence to keep up with changes and developments that occur in curriculum content in the learning process of students. The merdeka curriculum is the result of the government’s findings on the replacement of the previous curriculum, which gives students the freedom to develop their potential according to their talents and interests. This descriptive quantitative study aims to explore information about the understanding of physical education teachers on the implementation of the merdeka curriculum in junior high schools in Tarumajaya District, Bekasi Regency. The sampling technique was purposive sampling. This study involved 17 schools, with 21 physical education teachers as samples. The instrument used in this study was a questionnaire using a Likert scale and Google Forms media. The results of the study were analyzed using SPSS 23 through descriptive statistics. The data were categorized, then looked for percentages, and averaged (mean). The results of this study indicate the understanding of physical education teachers towards the implementation of an merdeka curriculum in junior high schools in Tarumajaya District with an average value of 73% which is then converted into a “Good Enough” category value. Based on the findings of this study, increasing teacher competence, especially pedagogical competence in Tarumajaya District, must be further optimized through increasing teacher understanding, providing adequate resources, reducing administrative burdens, increasing student motivation, and effective time management towards the focus of the Merdeka curriculum.